EU policies: an overview. From decision-making to implementation (Brussels, 2013)
"The European Union affects our daily lives. National governments implement regulations and laws which have been made at the EU level. The EU removes barriers between Member States, and we all profit from the freedom of movement of people and services in the EU. However, it is not always clear how these decisions are made, what policies are in place or the consequences these have for citizens and the EU as a whole. With much ongoing debate about reforming Europe, it is now more important than ever to know more about EU policies. This book contains 16 chapters on various EU policies, from financial topics to justice issues and foreign policy. It gives a broad and in-depth overview of the EU's and Member States' efforts to work together on issues that concern all of us, across the borders of the Member States. It provides information on the state of play and offers a glimpse of where we are headed. The book is intended for anyone who would like to learn more about EU policies, but especially for policymakers who wish to gain deeper knowledge of specific areas of EU policy."